2023
DOI: 10.1007/s00277-023-05294-3
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease and acute leukemia: one case report and an extensive review

Abstract: Population-based studies and case reports suggest that there may be an increased risk of acute leukemia associated with sickle cell disease (SCD). Following the description of a new case report, an extensive review of the literature identified 51 previously described cases. Most cases study showed myelodysplastic features confirmed, when available, by genetic markers such as chromosome 5 and/or chromosome 7 abnormalities and TP53 gene mutations. The increased risk of leukemogenesis is ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
(75 reference statements)
0
0
0
Order By: Relevance
“…Hemopathies can develop during all major forms of sickle cell disease. Acute leukemia has been described in all these major forms in France [6]. The homozygous SS form was the most common in our series.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…Hemopathies can develop during all major forms of sickle cell disease. Acute leukemia has been described in all these major forms in France [6]. The homozygous SS form was the most common in our series.…”
Section: Discussionsupporting
confidence: 49%
“…Olena O Seminog and al in England, in a study of administrative data, showed that within the black race, major sickle cell patients had a higher risk of developing cancer than a control cohort for cancers in general and particularly for hematological malignancies, but also for certain solid tumors [15]. In fact, the risk of hematological malignancy in sickle cell disease is 2 to 11 times as high as in the general population [6]. In fact, the increased risk of leukemogenesis in major sickle cell disease is thought to be multifactorial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations